Selecting the highest probability in binomial or multinomial trials - Levin, Bruce (Proc Natl Acad Sci U S A, 1981)
Some sequential procedures are considered for selecting the binomial population with largest success probability or for selecting the multinomial outcome with highest cell probability. Procedures with and without sequential elimination of inferior populations are evaluated with respect to the expected probability of the population selected.